Negotiating Love and Faith: Interfaith Marriage in Manado, Indonesia - Rosdalina Bukido; Edi Gunawan; Djamila Usup; Hayat Hayat (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2021)
Interfaith marriages in people’s lives have been practised in many areas in Indonesia, even if it’s not legally registered. The rule of law in Indonesia does not accommodate interfaith marriages. When interfaith marriage occurs, the registration system should follow the marriage registration process, either at the KUA (office of religious affairs) for Muslims or at the Civil Registry office for other religions. This study aims to analyse the practice of interreligious marriage in Manado and how spouses of different religions maintain a good marital relationship. This research employs a qualitative approach, collecting data through interviews with 30 informants who practice interfaith marriage in Manado City. This research found that many people in Manado consider interfaith marriage permissible. They argue that religion is a relationship between humans and God, while marriage is related to human beings. The family of different religions based their relationship on the principle of “Torang Samua Basudara” (we are bound through kinship). Based on this principle, the family avoids using religious symbols in their communication that can cause tension and disrupt harmony among family members. The principle of torang samua basudara serves as the basis for good communication within the family. This study contributes to the literature and policy debate on interfaith marriage in Indonesia by providing grounded evidence of how local values and everyday communication practices function as a practical social mechanism for sustaining interreligious households, even within a legal context that offers limited formal recognition.